Comparing α-Synuclein Fibrils Formed in the Absence and Presence of a Model Lipid Membrane: A Small and Wide-Angle X-Ray Scattering Study - Dubackic, Marija; Linse, Sara; Sparr, Emma; Olsson, Ulf (Frontiers in Soft Matter, 2022)
Amyloid fibrils are associated with a number of different neurodegenerative diseases. Detailed knowledge of the fibril structure will be of importance in the search of therapy and may guide experiments to understand amyloid formation. In this paper we investigate the morphology of alpha-synuclein amyloid fibrils, associated with Parkinson’s disease, formed under different conditions. In particular, we study, by means of small and wide-angle X-ray scattering, whether the presence of model lipid membranes affect the overall structure of the fibrils formed, motivated by the fact that amyloid fibrils in vivo are formed in a highly lipid-rich environment. Comparing fibrils formed in the presence of lipid with fibrils formed in their absence, show that the presence of lipids has no detectable effect on the fibril cross-section radius and that the characteristic beta-strand repeat distance of 4.7 Å of the extended intermolecular beta-sheets remains unaffected. We also show that the observed fibril radius is consistent with a fibril structure composed of two protofilaments. This indicates overall that the particular fibril structure, with their stacks of two-dimensionally folded alpha-synuclein molecules, represent a deep free energy minimum, not largely affected by the co-aggregation with lipids.